2022
DOI: 10.1186/s12954-022-00657-x
|View full text |Cite
|
Sign up to set email alerts
|

The changing landscape of pharmaceutical alternatives to the unregulated drug supply during COVID-19

Abstract: Background The dual COVID-19 and overdose emergencies amplified strain on healthcare systems tasked with responding to both. One downstream consequence of the pandemic in the USA and Canada was a surge in drug overdoses resulting from public health-restricted access to services and an increasingly toxic unregulated drug supply. This study aimed to describe changes implemented by programs prescribing pharmaceutical alternatives to the drug supply during the early stages of the COVID-19 pandemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…1 ), we identified 13 articles (representing 11 studies) that met our eligibility criteria. Two studies were associated with multiple reports ( Glegg et al, 2022 / McCrae et al, 2022 ; Suen et al, 2022 / Wyatt et al, 2022 ). Study characteristics are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ), we identified 13 articles (representing 11 studies) that met our eligibility criteria. Two studies were associated with multiple reports ( Glegg et al, 2022 / McCrae et al, 2022 ; Suen et al, 2022 / Wyatt et al, 2022 ). Study characteristics are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…While previous work has discussed clinical recommendations and protocols around iOAT [ 14 , 30 ], the COVID-19 pandemic required the iOAT clinic to make significant changes to the provision of services. For instance, under the guidance of their doctor, some clients were able to reduce their visit frequency and access take-home oral doses of medication or receive home delivery of oral medication if they were at severe risk of complications from COVID-19 [ 23 ]. Take-home injectable doses were not permitted at the time.…”
Section: Methodsmentioning
confidence: 99%
“…For clients receiving iOAT, the consequences of treatment disruption may be considerable, given the frequency of doses, the intensity of services, and the increasingly toxic drug supply in British Columbia that amplifies overdose risk. Emerging research with Canadian harm reduction and treatment providers during the pandemic has illustrated how staff had to ensure safe access to treatment while navigating provincial restrictions, service interruptions, increased staff responsibilities (e.g., cleaning, viral screening and testing), the development of new protocols, and their own risk of exposure to COVID-19 [ 23 ]. Recent work has also demonstrated how PWUD avoided harm reduction services during the pandemic due to COVID-19 risks [ 24 ], and how potential patients in British Columbia reduced their utilization of general healthcare services and of transit to healthcare systems during the pandemic [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond effects of the virus itself, the pandemic also threatened people's nancial, mental, and physical wellbeing-impacts that are magni ed for socioeconomically marginalized PWUD, including iOAT clients, who are more likely to experience nancial instability, homelessness, and decreased support for social, physical and mental health needs [4,27, 28]. However, despite myriad challenges in supporting PWUD and ensuring treatment access, the pandemic also presented new opportunities to develop clinic procedures and treatment protocols that address prior critiques and can be tailored to the needs of iOAT clients [18,23,29]. To investigate these complex changes and impacts, we draw on qualitative interviews with clients accessing iOAT and explore how the pandemic shaped their perspectives of and experiences with treatment, as well as make recommendations to support policymakers in the future planning and provision of iOAT programs.…”
mentioning
confidence: 99%